Pandangan Tuan Guru Lombok terhadap multi akad dalam muamalah maliyah kontemporer - Musawar Musawar (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
The concept of Hybrid Contract or “Multi Akad” is an ijtihad of the cholars to address the development of human life, especially in mu‘amalah aspect. It is understood as the merge of the two contracts or more in a contract. Therefore, many modern transactions use it and even in the last decade the scholars began to discuss about it’s validity. The conversation and debate about the validity of this Hybrid Contract appears not without reason, because of numbers of prophetic traditions, showed literarily that Hybrid Contract is forbidden in the transaction. Departing from that, this study answers three basic problems: the first is “how the concept of “Hybrid Contract” in view of Tuan Guru Lombok”, who became a role model for peoples of Lombok, because of they are as religious and community leaders. The second question is how an argumentation that built by Tuan Guru bout the “Multi Akad” in Islamic Law. While the third problem is how the typology Tuan Guru Lombok thought. This study is a qualitative research by maqasid al-Shari’ah  and the sociology law approaches, and this study is made with the method of interview to Tuan Guru who are determined by “purposive sampling” method, and so this research is supported by ocument data in the form of books, magazines and more. This study concluds that Hybrid Contract concept in Tuan Guru Lombok view is a contract containing two contracts or more in financial problems, both applicable in financial institutions shari‘ah or no. Surely, the concept of Hybrid Contract is a way to elude from “usury”. Regarding to Multi Akad in Islamic Law like “Dana Talangan Haji” at financial institutions shari‘ah,  Tuan Guru responded it by two argumentations: so that they are divide to two group: rejecter and endorser. And they are divided into 2 (two) typology: textual and textual progressive, the textual group understood that Hybrid Contract is unlawful or forbidden according to prophetic traditions texts and it was interpreted textually. While progressive textual tends to allow, even though they can not separate them self from the text of the prophetic traditions, but they also consider the development of thought, life, and environment.